Predicting soil hydraulic properties for binary mixtures – concept and application for constructed Technosols - M. Willaredt; T. Nehls; A. Peters (Hydrology and Earth System Sciences, 2023)
Constructed Technosols are an important means of substituting natural soil material, such as peat and geogenic material, for use in urban green infrastructure. One characteristic of Technosols important to their role in urban green infrastructure, specifically with respect to urban water management, is their soil hydraulic properties (SHPs). The SHPs depend on the composition of the constructed Technosols (e.g. their components and their mixing ratio). The diversity of possible components and the infinite number of mixing ratios practically prohibit the experimental identification of the composition needed to achieve suitable soil hydrological functions. In this study, we propose a compositional model for predicting the water retention curves (WRCs) of any binary mixture based on the measured WRCs of its two pure components only (basic scheme) or with one additional mixture (extended scheme). The unsaturated hydraulic conductivity curves (HCCs) are predicted based on the modelled WRCs. The compositional model is developed from existing methods for estimating the porosity of binary mixtures. The model was tested on four data sets of measured WRCs of different binary mixtures. The distribution of water and air in 50 cm high soil columns filled with these mixtures was predicted under hydrostatic conditions in order to assess their suitability for typical urban applications. The difference between the maxima of the pore size distributions ΔPSDmax (m) of the components indicates the applicability of the compositional approach. For binary mixtures with small ΔPSDmax, the water content deviations between the predicted and the measured WRCs range from 0.004 to 0.039 cm3 cm−3. For mixtures with a large ΔPSDmax, the compositional model is not applicable. The prediction of the soil hydraulic properties of any mixing ratio facilitates the simulation of flow and transport processes in constructed Technosols before they are produced (e.g. for specific urban water management purposes).